The role of citizen science in mosquito-borne disease surveillance and control: A scoping review - Nima Kianfar; Kimia Savoji; Xiao Huang; Di Yang; Abe Mollalo (PLoS ONE, 2026)
Background Mosquito-borne diseases (MBDs) pose substantial global health and economic burdens. Although conventional MBDs surveillance systems remain essential, they are often resource-intensive, uneven in coverage, and often insufficiently responsive to spatio-temporal variations in mosquito presence and risk. Citizen science, increasingly enabled by mobile and digital technologies, offers a scalable complement to expand surveillance reach and timeliness. However, existing reviews have not comprehensively integrated evidence across diverse dimensions of citizen science applied to MBDs surveillance and control. Methods We conducted a systematic search of PubMed, MEDLINE, CINAHL, Scopus, and Web of Science from January 1, 2000, to October 17, 2025, to identify peer-reviewed studies examining citizen science applications in MBDs surveillance and control. Data were extracted and synthesized on study characteristics, participation objectives, recruitment strategies, citizen-generated data and technologies, validation mechanisms, effort-bias handling, analytical approaches, public health outputs, reported biases and methodological limitations, and ethical and governance practices. Results Of 3,734 records identified, 61 studies met inclusion criteria, with most published after 2017 (93.4%). Studies were conducted in Europe (44.3%) and the Americas (21.3%), with minimal representation from Asia (3.3%). Malaria-related surveillance was most common (23.0%), followed by dengue (13.1%), with other mosquito-borne diseases examined only sporadically, including West Nile virus (4.9%), Usutu virus (1.6%), La Crosse virus (1.6%), and California serogroup viruses (1.6%). Most studies were conducted in urban settings (47.5%), followed by mixed urban–rural contexts (36.1%), with relatively few exclusively in rural areas (18.0%). Mosquito Alert was the most frequently reported platform (23.0%), followed by GLOBE Observer (13.1%) and iNaturalist (11.5%). Commonly reported outputs included trend analyses (52.5%), risk-factor identification (44.3%), spatial predictions (42.6%), hotspot mapping (19.7%), and risk modeling (16.4%). Reporting of ethical and governance practices was inconsistent across studies. Conclusions The growing body of evidence indicates that citizen science can enhance mosquito surveillance, particularly for monitoring invasive species and spatio-temporal trends. Nevertheless, gaps in methodological rigor, representativeness, and ethical transparency limit its broader operational use.